2023
DOI: 10.1139/apnm-2022-0456
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immune function in healthy adults: one-stop guide on the role of dietary fatty acids, gut microbiota-derived short chain fatty acids, and select micronutrients in combination with physical activity

Abstract: The immune system requires an adequate supply of nutrients, although current dietary recommendations may not account for optimal immune function in healthy adults. Nutrient inadequacies due to the growing influence of the western diet pose a risk for immune dysfunction. This review aims to determine the beneficial effects of supplementing: dietary fats, nutrients that modulate gut microbiota, and specific micronutrients, on systemic immune functions (concentrations of plasma cytokines, antibodies and acute pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 134 publications
0
1
0
Order By: Relevance
“…Additionally, lifestyle factors that improve CVH, such as a healthy diet, regular exercise, and smoking cessation, may also reduce the prevalence of PID. These behaviors are associated with lower systemic inflammation and improved immune function, [37,38] which can protect against infections that lead to PID.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lifestyle factors that improve CVH, such as a healthy diet, regular exercise, and smoking cessation, may also reduce the prevalence of PID. These behaviors are associated with lower systemic inflammation and improved immune function, [37,38] which can protect against infections that lead to PID.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation can weaken the immune system and contribute to various health issues. A diet rich in anti-inflammatory foods, such as fatty fish (like salmon and mackerel), olive oil, nuts, seeds, and colorful fruits and vegetables, can help mitigate inflammation and promote overall health [88]. The gut microbiome plays a crucial role in immune function and overall well-being [89].…”
Section: The Path To Resilience In the Post-covid Pandemic Eramentioning
confidence: 99%
“…A short-term randomized clinical trial has shown positive effects of a Mediterranean-like diet on CSF markers relevant to AD pathology [13]. Conversely, consumption of a so-called “Western” diet, which is high in saturated fats and simple sugars [14, 15], has been shown to increase systemic inflammation [16] and have detrimental neurobiological effects. Short term consumption of very high fat diets (60-75% fat) impairs attention and memory in clinical and preclinical studies [17].…”
Section: Introductionmentioning
confidence: 99%